Photocatalytic degradation of phenol using Nb-loaded ZnO nanoparticles - Kruefu V. (2014)
Niobium-loaded Zinc Oxide nanoparticles (Nb-loaded ZnO NPs) in the range of 20 and 40 nm were synthesized by Flame Spray Pyrolysis (FSP) technique. The crystalline phase, morphology and size of the nanoparticles were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM) and UV-vis spectroscopy. The specific surface area of the nanoparticles was measured by nitrogen adsorption (BET analysis). The unloaded ZnO and Nb-loaded ZnO NPs were found to have the clear spherical, hexagonal and rod-like morphologies. In this study, the photocatalytic activities of unloaded ZnO and Nb-loaded ZnO NPs were determined by studying the mineralization of phenol under UV light illumination. The results indicated that all Nb-loaded ZnO NPs have better photocatalytic activity than the unloaded ZnO nanoparticles. It was found that, 0.50 mol% Nb-loaded ZnO NPs exhibited the fastest response to the degradation of phenol.